1982
DOI: 10.1063/1.443177
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of relative concentrations and velocities of small clusters (n⩽40) in expanding water vapor flows

Abstract: The concentrations of water clusters (2⩽n⩽40) relative to the monomer concentration in expanding water vapor flows have been determined over a range of source pressures and temperatures by mass spectrometry. The corresponding directed flow velocities and thermal velocity distributions of the monomers and clusters of each size have been determined by mass-filtered time-of-flight (velocity) spectrometry. Relative concentration generally decreases exponentially with n. Translational thermal equilibrium ∼65 K prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The appearance of the ionized water clusters as protonated or deuterated species in the form of (H20),H + or (D20),D + ions observed here has already been seen in a variety of investigations [ 1,2,8]. But also the existence of unprotonated cluster ions (H20) + has been reported, which are produced by ionizing neutral (Ar)m(H20), clusters [5], by threshold photoionisation of water aggregates [29] or by using a special supersonic ion beam source [301.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The appearance of the ionized water clusters as protonated or deuterated species in the form of (H20),H + or (D20),D + ions observed here has already been seen in a variety of investigations [ 1,2,8]. But also the existence of unprotonated cluster ions (H20) + has been reported, which are produced by ionizing neutral (Ar)m(H20), clusters [5], by threshold photoionisation of water aggregates [29] or by using a special supersonic ion beam source [301.…”
Section: Discussionsupporting
confidence: 70%
“…The denominator of the last equation is the measured total ion signal Sk(O) of (1), so that by combining (1) and (3) with (2) finally the fragmentation probability f,k is given by fnk= SkY.k~ ~, SlcXnk.…”
Section: Size Selection and Fragmentation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…37 Substrate temperature during deposition varied with experiment from 77 to 140 K. Coalescence of some water molecules into gas-phase oligomers is expected to occur during beam formation. 38,39 However, the population of dimers and trimers relative to monomers reported for comparable expansion conditions is small; on the order of 1:20 and 1:100, respectively. 38,39 Following film growth, chlorodifluoromethane was deposited on ice surfaces held at 77 K utilizing a pure supersonic beam that was smaller than and centered on the water film.…”
Section: Methodsmentioning
confidence: 98%
“…Dreyfuss and Wachman 9 have reported that the minimum size for a doubly charged water cluster formed by electron impact from a neutral cluster is n =40, but the size of the neutral precursor could not be determined in their experiments.…”
mentioning
confidence: 96%